Clinical evaluation, motor performance and quality of life in patients affected by Soft Tissue Sarcomas undergoing surgical treatment: observational study - Demofonti, Andrea; Germanotta, Marco; Falchini, Francesca; Pavan, Arianna; Lattanzi, Stefania; Cortellini, Laura; Brunetti, Beniamino; Tenna, Stefania; Valeri, Alice; Pagnoni, Chiara; Passa, Roberto; Angelucci, Michela; et al. (Frontiers in Oncology, 2026)
Soft Tissue Sarcomas (STSs) are rare malignant tumors characterized by a marked histological heterogeneity. Their standard of care is the surgical resection with adjuvant therapies, but these interventions induce sensorimotor impairments, pain, and a reduction quality of life. In this context, systematic evidence on its role in STS patients is currently lacking. This prospective, multicenter, observational study aims to evaluate the effects of a personalized rehabilitation protocol on clinical characteristics, motor performance, and quality of life in patients undergoing surgery for STS of the trunk and lower limbs. Patients will be recruited and assessed at four time-points: baseline (pre-surgery), post-surgery (within 7 days post-surgery), pre-rehabilitation (within 30 days post-surgery), and post-rehabilitation (within 90 days post-surgery). Rehabilitation will combine conventional physiotherapy with robotic technologies, delivered over two daily sessions for approximately 60 days. The assessments will include gait analysis, clinical scales, and patient-oriented questionnaires. The primary endpoint will be the improvement in functional status quantified in terms of Toronto Extremity Salvage Score differentiated for the Lower Limb, while secondary outcomes will include biomechanical parameters, pain, and quality of life. This trial will represent the first study quantifying the impact of rehabilitation in patients with STS, with the potential to generate novel prognostic factors and provide an evidence-based framework for future tailored rehabilitation protocols.